Determinants of Profitability in Rural Banking: An Empirical Study of Malang Raya’s BPR - Yohana Agustina; Anggraeni Anggraeni (MediaTrend, 2025)
This study aims to analyze the factors influencing the profitability of Rural Banks (BPR) in the Malang Raya region and to examine the moderating role of gender diversity on the board of directors in the relationship between credit risk and profitability. This research employs a quantitative, causal approach using secondary data from the financial reports of 21 rural banks from 2019 to 2023, resulting in 125 observations. The dependent variable is profitability, measured by Return on Assets (ROA), while the independent variables include Credit Risk (Non-Performing Loan/NPL), Operational Efficiency (BOPO), Liquidity (Cash Ratio/CR), Loan to Asset Ratio (LAR), and Bank Size. The analysis was conducted using multiple linear regression with SPSS Version 27. The results indicate that NPL, BOPO, and Bank Size have a significant negative effect on ROA. Conversely, CR and LAR show a significant positive effect on ROA. The F-test confirms that the independent variables collectively have a significant impact on profitability, with the model explaining 92.4% of the variance in ROA. However, the study finds that gender diversity on the board of directors does not significantly moderate the negative relationship between NPL and ROA. These findings provide practical insights for rural bank management and policymakers, emphasizing the critical importance of credit risk management, operational efficiency, and strategic asset allocation for enhancing financial performance.